Characteristics of Appendicitis Patients in PKU Muhammadiyah Bantul Hospital: A Cross Sectional Study - Meidyastuti Izaz Hasna; Heriyanto Muhammad Junaidy; Sambada Taufiek Hikmawan Yuliarto Benni; Tejosukmono Ario (BIO Web of Conferences)
Appendicitis is an inflammation of the vermiform appendix. In 2019, worldwide there were estimated to be more than seventeen million cases of acute appendicitis. The difference in lifetime risk and incidence of appendicitis from various studies around the world raises a new possibility that there are differences in the characteristics of appendicitis in each population. This study aims to determine the main characteristics of appendicitis patients. This is an analytic-research with a cross sectional approach using total sampling technique with a total of 211 patients at PKU Muhammadiyah Bantul Hospital 2022. Appendicitis patients were predominantly female; in the age range of 20-44 years; the most common type was uncomplicated appendicitis; the average length of stay was 5 days; the average leukocyte was 10,616/ µL; the average thrombocytes count was 323,825/µL; and the most common complaint was abdominal pain. The characteristics of appendicitis patients are different in each population. Doctors are required to understand the disease and conduct a comprehensive examination so that patients can be treated properly.